Cone-Beam CT, CT and MRI for odontogenic tumors: a narrative review of imaging characteristics - Öçbe, Melisa (Ikatan Radiologi Kedokteran Gigi Indonesia, 2024)
Objectives: This review article aims to examine the role of cone-beam computed tomography (CBCT) in the diagnosis and management of odontogenic tumors. Additionally, it evaluates CBCT's efficacy in the assessment of both benign and malignant odontogenic tumors, including ameloblastoma, odontoma, and odontogenic myxoma. Review: This narrative review provides an in-depth analysis of CBCT imaging characteristics in the most common odontogenic tumors. The review highlights key CBCT features such as localization, peripheral structure, and internal architecture, emphasizing their impact on surrounding tissues. It compares the utility of CBCT with that of CT and MRI for the diagnosis of common odontogenic tumors, focusing on the strengths and weaknesses of each modality. The research questions addressed in this review include how CBCT can enhance diagnostic accuracy, what imaging characteristics are critical for differentiation between benign and malignant tumors, and how CBCT compares with traditional imaging methods in the context of maxillofacial tumor diagnostics. Conclusion: CBCT’s three-dimensional imaging capabilities provide clinicians with enhanced visualization of odontogenic tumor characteristics, aiding in accurate lesion localization, differentiation of tumor types, and treatment planning. CBCT is particularly useful for assessing the internal structure and peripheral boundaries of odontogenic tumors, improving the ability to distinguish between benign and malignant lesions. However, its limitations in soft tissue resolution underscore the continued importance of CT and MRI in comprehensive maxillofacial imaging.